Efficacy and Advantages of Spinal Anesthesia in Lumbar Disk Surgery - Akgun, Mehmet Yigit; Orak, Helin İlkay; Akgul, Mehmet Huseyin; Ates, Ozkan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Quality of life (QoL) may be affected due to various reasons such as low back or leg pains with accompanying neurologic problems. Lumbar disk surgery is one of the most common performed surgeries to relieve those symptoms. Various anesthetic techniques can be used safely to perform lumbar disk surgeries. Properties that make an anesthetic technique good are mainly the quick onset and returning of the effects. This large retrospective study with patients who have undergone lumbar disk surgery under spinal anesthesia aims to evaluate the perioperative and postoperative parameters of the spinal anesthesia and review the literature.Methods Cases operated under spinal anesthesia between January 2017 and December 2020 were investigated, and 617 patients who underwent simple lumbar disk surgery were included in the study. Demographic characteristics and American Society of Anesthesiologists (ASA) physical status of the patients were recorded. Visual analog scale (VAS) and QoLscores were obtained before and after the operation.Results There were 282 (45.7%) male and 335 (54.3%) female patients with a mean age of 39.48 ± 16.71 years (range: 18–58 years) at symptom onset. The mean operating time was 46.3 minutes (range: 22–68 minutes). Average blood loss was 85 mL (range: 55–125 mL). All the patients were mobilized 6 to 12 hours after surgery. In our patient group, there were both high- and normal-risk groups in terms of the ASA physical status. During the clinical follow-up, a statistically significant improvement was found for the VAS and QoL scores (p < 0.05).Conclusions In this large retrospective study, our results have confirmed that spinal anesthesia is at least comparable to general anesthesia and even superior to it in some aspects.
Keywords: spinal anesthesia; lumbar; disk; surgery